2005
DOI: 10.1111/j.1469-8137.2005.01374.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen supply affects arbuscular mycorrhizal colonization of Artemisia vulgaris in a phosphate‐polluted field site

Abstract: Summary• Root colonization by arbuscular mycorrhizal fungi (AMF) was investigated in industrially polluted grassland characterized by exceptionally high phosphorus levels (up to 120 g kg − 1 soil).• Along a pollution-induced nitrogen gradient, soil and tissue element concentrations of Artemisia vulgaris plants and their mycorrhizal status were determined. Additionally, we compared mycorrhization rates and above-ground biomass of A. vulgaris at N-fertilized and control plots in the N-poor area.• Despite high so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
2
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 50 publications
5
70
2
4
Order By: Relevance
“…Our results indicate that AM colonization may play an important role in successful establishment of C. jacea in grasslands. In line with previous studies (Sanders and Sheikh 1983;Smith and Read 1997;Blanke et al 2005), our results also indicate that soil water content, N:P ratio, P and K concentrations are important characteristics that promote AM colonization. Hence, these soil factors may be indicative of suitable conditions for establishment of C. jacea and eventually for other late-successional plant species.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results indicate that AM colonization may play an important role in successful establishment of C. jacea in grasslands. In line with previous studies (Sanders and Sheikh 1983;Smith and Read 1997;Blanke et al 2005), our results also indicate that soil water content, N:P ratio, P and K concentrations are important characteristics that promote AM colonization. Hence, these soil factors may be indicative of suitable conditions for establishment of C. jacea and eventually for other late-successional plant species.…”
Section: Discussionsupporting
confidence: 93%
“…The level of AM fungal colonization of plant roots and its effect on plant growth may vary depending on the composition and abundance of the AM fungal species (Van der Heijden et al 1998) and the available nutrients (Reynolds et al 2006). The significant correlations between abiotic soil characteristics, such as water content, N:P ratio, P and K concentrations, and the fraction of colonized root length containing arbuscules across aboveground and belowground environment types confirm the results of previous studies (Sanders and Sheikh 1983;Smith and Read 1997;Blanke et al 2005). Hence, the results suggest that plants are more likely to encounter circumstances that promote AM fungal colonization at sites with such abiotic soil conditions and have higher establishment rates.…”
Section: Discussionsupporting
confidence: 81%
“…2C). Increased colonization when N is limiting has previously been shown (18,19) and may interact with phosphate availability (18,20). In contrast to the P+AMF plants, G. hoi colonized the roots more rapidly (days 30 and 55) but G. mosseae colonized the roots to a greater extent thereafter (90 and 120 d; Fig.…”
Section: Resultsmentioning
confidence: 65%
“…Although plant available soil P was relatively high, it was considerably lower than in other studies where functional AMF were observed (e.g. Blanke et al 2005). Further insight may be gained in future studies by taking into account effects of P on the metabolic activity of AMF (Ezawa et al 2004;van Aarle et al 2005;Valentine and Kleinert 2007), extra-radicle growth (Olsson et al 2002;Cavagnaro et al 2005) and the abundance of arbuscules or other structures Jackson et al 2002;Cavagnaro et al 2003).…”
Section: Discussionmentioning
confidence: 84%